Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1749-7922-5-7
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of a Superior Mesenteric Artery Syndrome variant secondary to traumatic pseudoaneurysm

Abstract: Pseudoaneurysms related to the superior mesenteric artery (SMA) are a recognised complication of trauma to the vessel, and successful treatment with stenting has been previously described. We report the case of a patient who presented with obstruction of the fourth part of the duodenum secondary to a traumatic pseudoaneurysm, a hitherto unreported variant of superior mesenteric artery syndrome. Exclusion of the pseudoaneurysm and relief of the duodenal obstruction were simultaneously achieved by placement of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Therefore, beside angiography, it is considered as an alternative for detecting vascular diseases, such as pseudoaneurysms and aneurysms 1 . For this reason, most of true and false aneurysms are detected by CT and confirmed by angiography 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, beside angiography, it is considered as an alternative for detecting vascular diseases, such as pseudoaneurysms and aneurysms 1 . For this reason, most of true and false aneurysms are detected by CT and confirmed by angiography 3,6 .…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective report of 4 patients with SMAS treated with laparoscopic duodeno-jejunal manual lateral anastomosis by Wang Hui (2022) et al, it was noted that the patients had small surgical incisions, short hospital stay, rapid postoperative recovery, and no serious postoperative complications, which further suggests that laparoscopic duodeno-jejunal manual lateral anastomosis for the treatment of SMAS is effective, safe, and worthy of further clinical promotion. -Yong et al (2010) reported for the first time the successful interventional treatment of a trauma-induced rupture of an SMA pseudoaneurysm secondary to SMAS, which is a rare case in the clinic.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The etiology is often associated with trauma, inflammation, or iatrogenic injury related to previous surgical intervention as well as exceedingly rare reports of aneurysm and pseudoaneurysm degeneration of visceral vein bypass grafts. Repair of visceral artery pseudoaneurysms is encouraged in the elective setting, given the high morbidity and mortality associated with acute rupture 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13. We describe a physician-modified, fenestrated aortic endograft with suprarenal fixation to facilitate the repair of a growing aorta to SMA saphenous vein bypass graft pseudoaneurysm in a patient with a hostile abdomen.…”
mentioning
confidence: 99%